The Influence of The Work Environment on Employee Performance at Bank Syariah Indonesia in The Medan Raya Area - Al Ghazali, Syahnant; B, Mesra (PT. Multidisciplinary Press Indonesia, 2024)
The aim of this research is to determine and analyze the influence of the work environment on employee performance at Bank Syariah Indonesia in the Medan Raya area. This research was conducted using a causal associative quantitative approach. The sample used was 100 employees from a total of 287 employees who were taken at random using random sampling techniques. The research results show that the work environment has a positive and significant effect on employee performance. This is shown by the T-value of 16.165 > t table 1.66055 with a P-Value of 0.000 < 0.05. The regression coefficient shows that if the work environment is increased by 1 unit, employee performance will increase by 1,756 units assuming other variables remain constant. Apart from that, the results of the determination test show an Adjusted R Square value of 0.724 or 72.40%, which indicates that the work environment has a low influence on employee performance, while the remaining 27.60% is influenced by other factors that have not been studied. Thus, partially, the work environment has a positive and significant effect on the work of employees at Bank Syariah Indonesia in the Medan Raya area. This identifies that, meaning, improvements in the work environment can contribute to improving employee performance.